METHODOLOGY FOR THE DEVELOPMENT OF PHYSICAL QUALITIES BASED ON THE ANALYSIS OF THE COMPETITION ACTIVITIES OF YOUNG BELT WRESTLERS - Khakimov Shoyadbek Tolibovich (Innovate Conferences, 2025)
This article will cover the methodology for the development of physical qualities based on the analysis of the competition activities of young belt wrestlers. The study scientifically studied the technical and tactical actions of athletes in the competition process, their effectiveness and physical qualities such as speed, strength, endurance, agility and flexibility, which directly affect the results. Also, on the basis of competition analysis, individualization of training and methodological recommendations corresponding to the age, level of training, psychophysiological characteristics of the athlete and the experience of the competition were developed. The article reveals the theoretical and practical foundations of the effective organization of competition activities by the complex development of physical qualities in belt wrestlers. The results of the study are of practical importance for coaches training with young athletes and serve as a theoretical resource for further scientific and methodological research on Belt Wrestling.
Keywords: belt wrestling, young athletes, competition activities, physical qualities, technical and tactical training, methodology, coaching, sports training.